Exercise Physiology Across the Lifespan in Cystic Fibrosis - Shei, Ren-Jay; Mackintosh, Kelly A.; Peabody Lever, Jacelyn E.; McNarry, Melitta A.; Krick, Stefanie (Frontiers in Physiology, 2019)
Cystic fibrosis (CF), a severe life-limiting disease, is associated with multi-organ pathologies that contribute to a reduced exercise capacity. At present, the impact of, and interaction between, disease progression and other age-related physiological changes in CF on exercise capacity from child- to adult-hood is poorly understood. Indeed, the influences of disease progression and aging are inherently linked, leading to increasingly complex interactions. Thus, when interpreting age-related differences in exercise tolerance and devising exercise-based therapies for those with CF, it is critical to consider age-specific factors. Specifically, changes in lung function, chronic airway colonization by increasingly pathogenic and drug-resistant bacteria, the frequency and severity of pulmonary exacerbations, endocrine comorbidities, nutrition-related factors, and CFTR modulator therapy, duration, and age of onset are important to consider. Further studies are required that account for these factors and the changing landscape of CF in order to better understand how the evolution of CF disease impacts exercise (in)tolerance across the lifespan and thereby identify appropriate intervention targets and strategies.